Vitamin D Receptor Gene Polymorphisms Modify Cardiometabolic Response to Vitamin D Supplementation in T2DM Patients - Al-Daghri, Nasser M.; Mohammed, Abdul Khader; Al-Attas, Omar S.; Ansari, Mohammed Ghouse Ahmed; Wani, Kaiser; Hussain, Syed D.; Sabico, Shaun; Tripathi, Gyanendra; Alokail, Majed S. (Scientific reports, 2017)
There is conflicting evidence on the favorable effects of vitamin D supplementation on metabolic profile in Type 2 diabetes mellitus (T2DM) patients and this might be due to genetic variations in vitamin D receptors (VDRs). Thus, we studied the metabolic effects of a 12-month vitamin D supplementation in T2DM patients according to VDR polymorphisms. A total of 204 T2DM subjects received 2000 IU vitamin D3 daily for 12 months. Serum 25(OH)D and metabolic profiles were measured at baseline and after 12 months. VDR polymorphisms ( Taq-I, Bsm-I, Apa-I and Fok-I ) were identified using TaqMan genotyping assays. Vitamin D supplementation significantly increased HOMA β-cell function (p = 0.003) as well as significantly decreased triglycerides, total and LDL-cholesterol (p < 0.001). The lowest increment in 25(OH)D levels was detected in patients with Fok-I CC genotypes (p < 0.0001). With vitamin D supplementation, Taq-I GG genotype carriers showed significant improvements in triglycerides, LDL- and total cholesterol, insulin, HbA1c and HOMA-IR (p < 0.005, 0.01, < 0.001, < 0.005, 0.03 and 0.01, respectively). Similarly, Bsm-I TT genotype carriers showed significant improvements in triglycerides (p = 0.01), insulin and HOMA-IR (p-values < 0.05). In conclusion, improvements in metabolic profile due to vitamin D supplementation is influenced by VDR polymorphisms, specifically for carriers of Taq-I GG and Bsm-I TT genotypes.